Asymmetry in gait pattern following bicondylar tibial plateau fractures—A prospective one-year cohort study. Issue 7 (July 2017) - Elsoe, Rasmus; Larsen, Peter
Abstract: Introduction: Despite the high number of studies evaluating outcomes following tibial plateau fractures, the literature lacks studies including the objective assessment of gait pattern. The purpose of the present study was to evaluate asymmetry in gait patterns at 12 months after frame removal following ring fixation of a tibial plateau fracture. Patients and methods: The study design was a prospective cohort study. The primary outcome measurement was the gait patterns 12 months after frame removal measured with a pressure-sensitive mat. The mat registers footprints and present gait speed, cadence, as well as temporal and spatial parameters of the gait cycle. Gait patterns were compared to a healthy reference population. Results: Twenty-three patients were included with a mean age of 54.4 years (32–78 years). Patients presented with a shorter step-length of the injured leg compared to the non-injured leg (asymmetry of 11.3%). Analysis of single-support showed shorter support time of the injured leg compared to the non-injured leg (asymmetry of 8.7%). Moreover, analysis of swing-time showed increased swing-time of the injured leg (asymmetry of 8.9%). Compared to a healthy reference population, increased asymmetry in all gait patterns was observed. The association between asymmetry and health-related quality of life (HRQOL) showed moderate associations (single-support: R = 0.50, P = 0.03; step-length: R = 0.43, P = 0.07; swing-time: R = 0.46, P = 0.05). Conclusion: Compared to a healthy reference population, gait asymmetry is common 12 months after frame removal in patients treated with external ring fixation following a tibial plateau fracture of the tibia.